EVOLUTION OF BRAND IMAGE IN THE DIGITAL ERA: A BIBLIOMETRIC ANALYSIS OF SOCIAL MEDIA AND INFLUENCER MARKETING - Lohchab, Kirti; Chauhan, Anand; Kumar, Raj (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The purpose of this paper is to identify the changes in brand image subject to social media and influencer marketing. Through the bibliometric analysis of the academic works, the present study outlines the recurrent themes, trends, and co-authorship collaboration networks that have characterized the brand image literature within the digital marketing environment. Design/Methodology/Approach: The bibliometric analysis with regard to publications from 1991 till 2023 has been developed. Referring to tools namely biblioshiny (RStudio) and VOS viewer, 620 documents were reviewed with equal subdivision in journals, books and conference papers respectively with concentration on keywords, authors’ cooperation and institutes. Findings: The work shows increased popularity of the efforts geared towards evaluating brand image, facilitated by the development of the social media and influencer marketing concept. Average number of countries that have been involved in the research and high citation rates for these topics prove the significance of these topics to the researchers. Some of the relevant future trend areas are pointed out with reference to the topics like application of the AI in the sphere of marketing and analysis of consumers’ behavior. Originality/Value: This paper specifically provides a detailed bibliometric analysis of brand image and specifically how the digital age has influenced this research area through social media and influencer marketing. It points at major works, authors and institutions, which makes it useful for researcher and practitioners, who is interested in the development of the concept of branding in the new media context.